Unveiling the Dynamics of African Post-Colonial Administration: A Holistic Analysis of Devil on the Cross - Diallo, Souleymane (Journal La Sociale, 2023)
Through the frame frequency of the imported state and the westernization of the African political order, the social construction of the African bureaucracy appears as a structural device of abstraction, exploitation, and brutality. Then, through the frame of reference with the importation of conceptual juridical coordination and perceptual representative consensus, the African public administration enhances a frameshift transformation and a succession of causality. Therefore, in combinatorial and transactional analysis, the framework of Devil On The Cross progresses in a method of empirical processing decomposition. Within this respect, the elemental and pure imaginary of the African administration proceeds as a functional derivative governmentality and a colonial functional inception power. Subsequently, with its interaction design, processing system, and volume technique, the realm of Devil on The Cross inserts a paradigmatic analysis and a value engineering within which this African administration happens as an characteristic structural formula and an inefficient relational frame theory. Moreover, within the space-time continuum, the configuration management and the linear configuration programming of the African management apparatus, Devil On The Cross becomes a holomorphic function and an analytic continuation that reveal the anachronism nature and the asynchronous system of the African post-colonial administration.